Building trust in open educational resources for multiliteracies in English and Applied Linguistics - Hautemo, Aletta; Iithindi, Sylvia (Critical Studies in Teaching and Learning, 2025)
The paper examines the issue of trust in adopting open educational resources (OER) to develop multiliteracies in the field of English and Applied Linguistics. The goal is to intentionally integrate best practices in teaching, ultimately transforming educational resources to be more open, inclusive, equitable, and accessible. A mixed-method approach was employed, purposively involving 22 postgraduate English and Applied Linguistics students. Data collection methods included closed-ended questionnaires and open-ended written reflections. Participants wrote reflections that assessed the credibility of OER, contributing to a broader social understanding of their personal experiences with the phenomenon and focusing on the systemic implications that hinder social transformation and trust-building around OER. The data analysis was themed to assess and develop strategies to facilitate a radical paradigm shift in enhancing the trustworthiness of adopting and using OER across diverse learning contexts. The findings reveal that OER provides a wealth of tools that empower students to explore diverse genres, fostering the development of multiliteracies. Integrating OER into multiliteracies can create an engaging and dynamic reading environment, ultimately enhancing students' reading habits. However, users may hesitate to fully embrace OER due to concerns about the quality and reliability of the resources, leading to a lack of confidence. Therefore, trust emerges as a crucial factor of contestation in the collaborative process of OER creation, adaptation, use, and sharing that contributes to knowledge-building processes and practices.